Development of Biocomposites with Antioxidant Activity Based on Red Onion Extract and Acetate Cellulose - Guarda-Moraga, A; Galotto-Lopez, M; Navarro-Lisboa, R; Lopez de Dicastillo-Bergamo, A (Multidisciplinary Digital Publishing Institute (MDPI), 2015)
Antioxidant biocomposites have been successfully developed from cellulose acetate, eco-friendly triethyl citrate plasticizer and onion extract as a source of natural antioxidants. First, an onion extraction process was optimized to obtain the extract with highest antioxidant power. Extracts under absolute ethanol and ethanol 85% were the extracts with the highest antioxidant activity, which were the characterized through different methods, DPPH (2,2-diphenyl-1-picrylhydrazyl) and ABTS (2,2ʹ-azinobis(3-ethylbenzothiazoline-6-sulphonate)), that measure radical scavenger activity, and polyphenolic and flavonoid content. Afterwards, the extract was incorporated in cellulose acetate as polymer matrix owing to develop an active material intended to oxidative sensitive food products packaging. Different concentrations of onion extract and plasticizer were statistically studied by using response surface methodology in order to analyze the influence of both factors on the release of active compounds and therefore the antioxidant activity of these materials. © 2015 by the authors; licensee MDPI, Basel, Switzerland.